Autoimmunity in Parkinson's Disease: The Role of α-Synuclein-Specific T Cells - Garretti, Francesca; Agalliu, Dritan; Lindestam Arlehamn, Cecilia S.; Sette, Alessandro; Sulzer, David (Frontiers in Immunology, 2019)
Evidence from a variety of studies implicates a role for the adaptive immune system in Parkinson’s disease (PD). Similar to multiple sclerosis (MS) patients who display a high number of T cells in the brain attacking oligodendrocytes, the midbrain of PD patients shows higher numbers of T cells than healthy age-matched controls. Mouse models of the disease also show the presence of T cells in the brain, which may be essential to recapitulate these models. The role of these infiltrating T cells in the propagation of disease is controversial; however, recent studies indicate that they may be autoreactive in nature, recognizing disease-altered self-proteins as foreign. T cells of PD patients can generate an autoimmune response to α-synuclein, a protein that is aggregated in PD. α-Synuclein and other proteins are post-translationally modified in an environment in which protein processing is altered, possibly leading to the generation of neo-epitopes, or self-peptides that have not been identified by the host immune system as non-foreign. Infiltrating T cells may be responding to such modified proteins.. Genome-wide association studies (GWAS) have moreover shown associations of PD with haplotypes of major histocompatibility complex (MHC) class II genes, and a polymorphism in a non-coding region that may increase MHC class II in PD patients. We speculate that the inflammation observed in PD may play both pathogenic and protective roles. Future studies on the adaptive immune system in neurodegenerative disorders may elucidate steps in disease pathogenesis and assist with the development of both biomarkers and treatments.